Characteristics of extreme precipitation and precipitation estimation under different return periods in the Pamir Plateau - Li, Shujuan; Chen, Jing; Huo, Hong; Shang, Huaming; Lu, Xinyu; Zhang, Tongwen; Yao, Junqiang; Mao, Weiyi; Yao, Mengying; Ma, Liyun; Tuoliewubieke, Dilinuer (Frontiers in Earth Science, 2026)
IntroductionAs the “Water Tower of Central Asia,” the Pamir Plateau is critical for regional water security. Research on its extreme precipitation is therefore vital for water resource assessment, hydrological modeling, and disaster risk planning.MethodsUsing daily observational data and the Peak Over Threshold method, we constructed extreme precipitation series across the region. Forty-six statistical functions were applied to select the optimal fit for return period analysis at each station, enabling the estimation of precipitation amounts across eight return periods.Results(1) Extreme precipitation exhibits non-synchronous variation with annual precipitation. While about two-thirds of stations show increasing daily extremes, 42.9% show opposite trends between the two. Spatially, extremes are lowest in the southwestern plateau and highest in the Fergana Basin. (2) The contribution of extreme precipitation to multiyear totals ranges from 24.0% to 40.0%, peaking at 88.13% in some years, and shows a significant negative correlation with annual precipitation. Stations above 3,400 m record higher amounts, suggesting a maximum precipitation belt above the previously recognized 2,000–3,500 m range. (3) Stations with annual precipitation below 150 mm exhibit the strongest extremes, where a single 50–100 year return period event can approach or exceed half of the local annual total. (4) The Wakeby and Gen.Pareto distributions show the widest applicability for the region, each optimal for 36% of stations. Extreme precipitation increases 2–3-fold as return periods extend from 2 to 100 years, reaching a maximum of 68.1 mm.DiscussionThese findings highlight significant flood risks and ecological vulnerability, particularly in arid areas with fragile ecosystems. The identified spatial patterns and the lack of a universally applicable distribution function underscore the complexity of extreme precipitation in the Pamir Plateau. This work provides a critical foundation for improved water resource management and climate adaptation strategies in Central Asia.